2019
DOI: 10.1002/cphc.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polymethine Dyes with Detonation Nanodiamonds

Abstract: Among cationic, anionic, and merocyanine polymethine dyes, the binding to detonation nanodiamond (DND) colloid particles in hydrosol occurs only for negatively charged dye species. This, in view of the positive ζ‐potential of the DND used in this study, suggests the predominance of electrostatic interactions over other intermolecular forces in such systems. Indeed, after decorating the merocyanine and the cationic dye by one and two negatively charged sulfopropyl groups, respectively, so that the net charge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(91 reference statements)
1
5
0
3
Order By: Relevance
“…It was also found that the lasing threshold can be lowered and the quality of generation of laser radiation can be improved in cationic polymethines by using the localized plasmon resonance of noble metal nanoparticles (NPs) [5]. Nanoparticles can also have a significant effect on the photophysical properties of neutral polymethines, such as merocyanine dyes [6], as was shown recently [7,8]. However, in spite of this, merocyanines have not been studied as active laser media in the presence of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the lasing threshold can be lowered and the quality of generation of laser radiation can be improved in cationic polymethines by using the localized plasmon resonance of noble metal nanoparticles (NPs) [5]. Nanoparticles can also have a significant effect on the photophysical properties of neutral polymethines, such as merocyanine dyes [6], as was shown recently [7,8]. However, in spite of this, merocyanines have not been studied as active laser media in the presence of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Нормовані спектри флюоресценції ВКТ1 за різних довжин хвилі збудження ( exc ). 3 СИНТЕЗА ТА СПЕКТРАЛЬНІ ВЛАСТИВОСТІ ÔЛЮОРЕСЦЕНТНИХ СТРÓКТÓР 645 перспективною методою одержання світлоперетворювальних матеріалів з новими корисними властивостями [9][10][11]. Ó даній роботі ми дослідили можливу взаємодію ВКТ з трьома поліметиновими барвниками 1, 1a та 2:…”
Section: вивчення взаємодії одержаних вкт і поліметинових барвників уunclassified
“…As a result of the production method (detonation), the sp 3 diamond core is always covered with a few layers of sp 2 carbon. This allows surface functionalization, allowing the formation of electrostatic [4][5][6] or covalent linkages, and facilitating the preparation of hybrid organic-nanodiamond materials [7,8]. This has greatly contributed to a widespread application of these organic-nanodiamond carbon materials [9][10][11][12][13][14], in biomedicine [15][16][17][18], nonlinear optical materials [19,20], energy devices [21,22] and tribology [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Among the several hybrids consisting of ND and organic materials, we highlight those bearing tetrapyrrolic macrocycles, such as porphyrins [25] and phthalocyanines [1][2][3][4][5][6]. These are compounds with unique properties, used in a large range of biomedical applications [26][27][28][29] and as highly efficient catalysts in a variety of reactions [30,31].…”
Section: Introductionmentioning
confidence: 99%